Synergistic impact of cerium oxide nano additive along with produced-HHO gas on CI engine behaviors running with pyrolyzed waste plastic oil - El-Shafay, A. S.; Fareed, Aisha F.; Agbulut, Uemit; Mujtaba, M. A.; Riaz, Fahid; Gad, M. S. (ELSEVIER, 2025)
The gain sustainable energy from waste plastic decreases the dependence on fossil fuel. Waste plastics were converted to oil by pyrolysis which combined with pure diesel in 20 % volumetrically. Oil's physical and chemical characteristics were measured. Nano cerium oxide was added to the oil mixture at concentrations of 25, 50, and 100 ppm. Oxyhydrogen gas (HHO) was formed by water electrolysis using an alkaline electrolyser at 0.5 litres per minute. Experiments were run at engine speed of 3000 rpm and load variation. When HHO was added to pyrolysis oil, CeO2 mixtures (P20C25, P20C50, and P20C100) improved thermal efficiency by 11, 12, and 13 % and reduced specific fuel consumption by 10, 11, and 14 %, respectively. Addition of 25, 50, and 100 ppm nano CeO2 to pyrolysis oil with HHO resulted in notable decreases of CO concentrations by 15 %, 19 %, and 22 % about P20. There were decreases in smoke concentrations of 25 %, 29 %, and 32 %, along with notable decreases in hydrocarbon emissions of 27 %, 30 %, and 35 % for P20C25 + HHO, P20C50 + HHO, and P20C100 + HHO, respectively. Enrichment with hydroxy to oil blend that contained 25, 50, and 100 ppm of nanoparticles reduced NOx emissions by 19 %, 22 %, and 26 %, respectively. There were improvements in heat release rate and cylinder pressure for oil mixture with nano additives and hydroxy. Pyrolysis oil from waste plastic that has been enhanced with 100 ppm cerium oxide and HHO can be applied to reduce exhaust pollutants, improve combustion, and boost engine performance.
Keywords: Waste plastic; Cerium oxide; HHO; Engine Performance; Combustion; Emissions; CATALYTIC PYROLYSIS; DIESEL; EMISSION; PERFORMANCE; ELECTROLYZER; Engineering